2023
DOI: 10.1101/2023.02.14.528208
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Template-assisted covalent modification of DCAF16 underlies activity of BRD4 molecular glue degraders

Abstract: Small molecules that induce protein-protein interactions to exert proximity-driven pharmacology such as targeted protein degradation are a powerful class of therapeutics. Molecular glues are of particular interest given their favorable size and chemical properties and represent the only clinically approved degrader drugs. The discovery and development of molecular glues for novel targets, however, remains challenging. Covalent strategies could in principle facilitate molecular glue discovery by stabilizing the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
54
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(61 citation statements)
references
References 69 publications
4
54
0
Order By: Relevance
“…Several recent independent studies with specific protein targets and compounds have also revealed the possibility for converting protein-targeting ligands into molecular glue degraders through subtle chemical changes. These examples include: (1) CR8, a close analog of the nondegradative CDK12 inhibitor (R)- roscovitine, that engages in a ternary complex between CDK12-cyclin K and the CUL4 adaptor protein DDB1, leading to cyclin K ubiquitination and degradation; (2) BI-3802, a BCL6 inhibitor that was discovered to be a degrader of BCL6 through recognition of BI-3802-mediated polymerization filaments by the SIAH1 E3 ligase; (3) GNE-0011, MMH1, and MMH2, reversibly and irreversibly acting analogs of the nondegradative BRD4 inhibitor JQ1, that led to BRD4 degradation through ternary complex formation with the cullin E3 ligase substrate receptor DCAF16. …”
Section: Introductionmentioning
confidence: 99%
“…Several recent independent studies with specific protein targets and compounds have also revealed the possibility for converting protein-targeting ligands into molecular glue degraders through subtle chemical changes. These examples include: (1) CR8, a close analog of the nondegradative CDK12 inhibitor (R)- roscovitine, that engages in a ternary complex between CDK12-cyclin K and the CUL4 adaptor protein DDB1, leading to cyclin K ubiquitination and degradation; (2) BI-3802, a BCL6 inhibitor that was discovered to be a degrader of BCL6 through recognition of BI-3802-mediated polymerization filaments by the SIAH1 E3 ligase; (3) GNE-0011, MMH1, and MMH2, reversibly and irreversibly acting analogs of the nondegradative BRD4 inhibitor JQ1, that led to BRD4 degradation through ternary complex formation with the cullin E3 ligase substrate receptor DCAF16. …”
Section: Introductionmentioning
confidence: 99%
“…42 Another example utilized an innovative template-directed covalent modification approach to deliver a covalent E3 glue via an electrophilic BRD4 ligand to a specific cysteine in DCAF16, circumventing many of the specificity challenges of covalent E3 ligands, effectively stabilizing the ternary complex to enable protein degradation. 43 Through modeling, we can examine any E3 and target system and probe various steps in the TPD reaction, including the kinetics of PROTAC binding and covalent bond formation to the E3/target, ternary complex formation, and ubiquitination, leading to degradation. Requirements of k inact /K i for a particular system will depend on target and E3 half-lives, compound PK, stoichiometry between E3 and target, and the degradation threshold for efficacy.…”
Section: ■ Resultsmentioning
confidence: 99%
“…Notably, a recent study extended a covalent chemoproteomic approach to identify a novel covalent molecular glue degrader EN450 that directly engages an E2 ubiquitin ligase UBE2D that then recruits, ubiquitinates, and degrades the NFKB1 transcription factor leading to antiproliferative effects in cancer cells . Another example utilized an innovative template-directed covalent modification approach to deliver a covalent E3 glue via an electrophilic BRD4 ligand to a specific cysteine in DCAF16, circumventing many of the specificity challenges of covalent E3 ligands, effectively stabilizing the ternary complex to enable protein degradation . Through modeling, we can examine any E3 and target system and probe various steps in the TPD reaction, including the kinetics of PROTAC binding and covalent bond formation to the E3/target, ternary complex formation, and ubiquitination, leading to degradation.…”
Section: Discussionmentioning
confidence: 99%
“…Beyond monomeric MGs, bifunctional PROTAC-like molecules were recently found to be able to glue the target protein Brd4 to the E3 ligase DCAF16 by intramolecularly bridging two domains of the target protein and anchoring an intrinsic Brd4-DCAF16 protein–protein interaction, without directly engaging DCAF16, leading to very efficient Brd4 degradation (see refs. for related papers published around the same time). Phenotypic screens in cells carrying E3 ligase mutation, hyponeddylation mutation, or locking Cullin ligases in an active conformation have also successfully identified new MG degraders.…”
Section: Targeted Protein Degradationmentioning
confidence: 99%